Ferritic stainless steel and method for producing same
Patent Information
- Application Number
- JP2021034809
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-04
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2041-03-04
AI Technical Summary
【0008】 本発明の一態様によれば、低コストで製造可能であり、耐赤スケール性に優れたフェライト系ステンレス鋼を実現することができる。
Smart Images

Figure 0007645098000003 
Figure 0007645098000001 
Figure 0007645098000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel having excellent resistance to red scale. [Background technology]
[0002] When ferritic stainless steel is used for applications such as exhaust gas path components, stove combustion, fuel cell components, etc., it is usually heated to high temperatures of 300 to 900°C during use. In addition, in the above applications, the ferritic stainless steel is used in an environment containing water vapor, so red scale (Fe-based oxides) may be generated. In some cases, this generated red scale may scatter and adhere to other parts, causing adverse effects, and there is a risk of reducing high-temperature strength due to thinning caused by oxidation. Therefore, ferritic stainless steel that has red scale resistance in a high-temperature water vapor atmosphere is desired. Conventionally, various methods have been known for improving high red scale resistance.
[0003] Patent Documents 1 and 2 describe a technique for strengthening the oxide film of ferritic stainless steel by adding Si to promote the diffusion of Cr and increase the amount of Cr-based oxides produced, thereby improving the steam oxidation resistance and red scale resistance of the ferritic stainless steels described in Patent Documents 1 and 2. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-160844 A [Patent Document 2] JP 2003-160842 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the ferritic stainless steels described in Patent Documents 1 and 2 require a high Si content, which results in high production costs.
[0006] An object of one aspect of the present invention is to provide a ferritic stainless steel that can be produced at low cost and has excellent red scale resistance. [Means for solving the problem]
[0007] In order to solve the above problems, a ferritic stainless steel according to one embodiment of the present invention contains, by mass%, C: 0.040% or less, Si: 0.01 to 2.0% or less, Mn: 0.03 to 2.0%, P: 0.05% or less, S: 0.005% or less, Ni: 1.5% or less, Cr: 13 to 26.0%, Cu: 2.0% or less, N: 0.040% or less, Mo: 2.5% or less, Nb: 1.0% or less, Ti: 0.5% or less, and Al: 0.002 to 0.50% or less, with the balance being Fe and unavoidable impurities, and the integrated C concentration measured at 0.0025 μm intervals from the surface to a depth of 0.1 μm is 200 wt% or less. Effect of the Invention
[0008] According to one aspect of the present invention, a ferritic stainless steel that can be manufactured at low cost and has excellent red scale resistance can be realized. [Brief description of the drawings]
[0009] [Figure 1] 1 is a flowchart showing an example of a method for producing a ferritic stainless steel according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the embodiments of the present invention will be described. Note that the following description is for better understanding of the gist of the invention, and does not limit the present invention unless otherwise specified. In this application, "A to B" indicates A or more and B or less.
[0011] In addition, in this specification, the term "stainless steel" refers to a stainless steel material whose specific shape is not limited. Examples of the stainless steel material include steel plates, steel pipes, and bar steel.
[0012] <Carbon concentration near the surface> In the production of ferritic stainless steel, oils such as mineral oil or other rolling oils are used for lubrication and cooling when cold rolling is performed using a rolling mill, and the oil adheres to the steel sheet. If annealing is performed with the oil adhered to the steel sheet, carbon will concentrate on the surface of the ferritic stainless steel. Through extensive research, the present inventors have found that if carbon is concentrated on the surface of the steel sheet, the red scale resistance of the ferritic stainless steel will decrease, and have completed the ferritic stainless steel of the present invention.
[0013] That is, the inventors have found that the red scale resistance of ferritic stainless steel is improved by lowering the carbon concentration near the surface, in other words, by not concentrating carbon near the surface. This is believed to be due to the following reasons. That is, when the carbon concentration near the surface is low, the Cr concentration near the surface is high. As a result, chromium oxide Cr2O3 is easily formed near the surface. The chromium oxide improves the red scale resistance of ferritic stainless steel.
[0014] Specifically, the ferritic stainless steel of the present invention has a cumulative carbon concentration of 200 wt% or less measured at 0.0025 μm intervals from the surface to a depth of 0.1 μm. This configuration allows the ferritic stainless steel of the present invention to have a high chromium concentration near the surface. More specifically, the average Cr concentration from the surface to a depth of 1 μm can be set to 13.0 wt% or more. As a result, the ferritic stainless steel of the present invention has high red scale resistance.
[0015] <Composition of ferritic stainless steel> The composition of components contained in the ferritic stainless steel according to one embodiment of the present invention is as follows. In addition to the components shown below, the ferritic stainless steel is made of iron (Fe) or small amounts of impurities that are inevitably mixed in (unavoidable impurities).
[0016] (Chromium: Cr) Cr is an essential element for forming a passive film and ensuring corrosion resistance. It is also effective for ensuring red scale resistance. However, excessive Cr content increases material costs and causes a decrease in toughness. Therefore, in one embodiment of the ferritic stainless steel of the present invention, the Cr content is 13.0 to 26.0 mass%, and preferably 16.0 to 22.0 mass%.
[0017] (Silicon: Si) Silicon is an element effective in improving red scale resistance. However, excessive silicon content can cause a decrease in toughness and workability. Therefore, in the ferritic stainless steel according to one embodiment of the present invention, the silicon content is 0.01 to 2.0 mass%, preferably 0.02 to 1.0 mass%, and more preferably 0.05 to 0.8 mass%.
[0018] (Copper: Cu) Cu is an element added to ensure high-temperature strength. However, excessive Cu content destabilizes the ferrite phase and increases material costs. Therefore, in one embodiment of the ferritic stainless steel of the present invention, the Cu content is 2.0 mass% or less, and preferably 0.01 to 0.40 mass%.
[0019] (Molybdenum: Mo) Mo is an element added to ensure high-temperature strength and red scale resistance. However, excessive Mo content hardens the material, reduces workability, and increases material costs. Therefore, in one embodiment of the ferritic stainless steel of the present invention, the Mo content is 2.5 mass% or less, and preferably 0.02 to 1.5 mass%.
[0020] (Niobium: Nb) Nb is an element added to ensure high-temperature strength. However, excessive Nb content can deteriorate workability and toughness. Therefore, in the ferritic stainless steel according to one embodiment of the present invention, the Nb content is 1.0 mass% or less, preferably 0.005 to 0.7 mass%, and more preferably 0.010 to 0.5 mass%.
[0021] (Titanium: Ti) Ti is an element that can convert ferritic stainless steel into a ferritic single layer at 900 to 1000°C by reacting with C and / or N, improving red scale resistance and workability. However, excessive Ti content can deteriorate workability and surface quality. Therefore, in one embodiment of the ferritic stainless steel of the present invention, the Ti content is 0.5 mass% or less, preferably 0.01 to 0.25 mass%.
[0022] (Manganese: Mn) Mn is an element that improves the adhesion of scale in ferritic stainless steel. However, excessive Mn content destabilizes the ferrite phase and promotes the generation of MnS, which acts as a corrosion starting point. Therefore, in one embodiment of the ferritic stainless steel of the present invention, the Mn content is 0.03 to 2.0 mass%, preferably 0.005 to 1.0 mass%, and more preferably 0.05 to 0.8 mass%.
[0023] (Carbon:C) Excessive C content increases the amount of carbides and reduces corrosion resistance, so in the ferritic stainless steel according to one embodiment of the present invention, the C content is 0.040 mass% or less, preferably 0.001 to 0.030 mass%, and more preferably 0.003 to 0.020 mass%.
[0024] (Rin:P) Excessive P content reduces workability, so in the ferritic stainless steel according to one embodiment of the present invention, the P content is 0.05 mass% or less, preferably 0.005 to 0.040 mass%, and more preferably 0.010 to 0.035 mass%.
[0025] (Sulfur: S) Excessive S content promotes the formation of corrosion initiation points in ferritic stainless steels, so the S content in the ferritic stainless steel in one embodiment of the present invention is 0.005 mass% or less, preferably 0.0001 to 0.003 mass%, and more preferably 0.0003 to 0.002 mass%.
[0026] (Nickel: Ni) Ni is an element that improves the corrosion resistance of ferritic stainless steel. However, excessive Ni content destabilizes the ferrite phase and increases material costs. Therefore, in the ferritic stainless steel according to one embodiment of the present invention, the Ni content is 1.5 mass% or less, preferably 0.02 to 1.0 mass%, and more preferably 0.04 to 0.4 mass%.
[0027] (Nitrogen: N) Excessive N content forms nitrides with other elements, leading to hardening, so in the ferritic stainless steel according to one embodiment of the present invention, the N content is 0.040 mass% or less, preferably 0.001 to 0.030 mass%, and more preferably 0.003 to 0.020 mass%.
[0028] (Aluminum: Al) Al is an element effective for improving the corrosion resistance of ferritic stainless steel and for improving red scale resistance. Also, Al is an element effective as a deoxidizer during steelmaking. However, if Al is contained excessively, there is a possibility that the surface quality may deteriorate. Therefore, in one embodiment of the ferritic stainless steel of the present invention, the Al content is 0.002 to 0.50 mass%, and preferably 0.010 to 0.1 mass%.
[0029] <Other ingredients> The ferritic stainless steel according to one embodiment of the present invention may further contain one or more of 0.01 mass% or less of B, 0.0002 mass% or more and 0.0030 mass% or less of Ca, 0.001 mass% or more and 0.5 mass% or less of Hf, 0.01 mass% or more and 0.40 mass% or less of Zr, 0.005 mass% or more and 0.50 mass% or less of Sb, 0.01 mass% or more and 0.30 mass% or less of Co, 0.01 mass% or more and 2.0 mass% or less of W, 0.001 mass% or more and 1.0 mass% or less of Ta, 0.002 mass% or more and 1.0 mass% or less of Sn, 0.0002 mass% or more and 0.30 mass% or less of Ga, 0.001 mass% or more and 0.20 mass% or less of rare earth elements, and 0.0003 mass% or more and 0.0030 mass% or less of Mg.
[0030] (Tungsten: W) W is an element added to ensure high-temperature strength. However, excessive W content increases material costs. Therefore, in one embodiment of the ferritic stainless steel of the present invention, 0.01 mass % to 2.0 mass % of W may be added as necessary.
[0031] (Boron: B) B is an element that improves the secondary workability of molded products manufactured using ferritic stainless steel. However, excessive B content may lead to the formation of compounds such as Cr2B, which may deteriorate red scale resistance. Therefore, in the ferritic stainless steel according to one embodiment of the present invention, 0.01 mass% or less of B may be added as necessary, and preferably 0.002 mass% or more and 0.003 mass% or less of B may be added.
[0032] (Calcium: Ca) Ca is an element that promotes high-temperature oxidation resistance. In the ferritic stainless steel according to one embodiment of the present invention, 0.0002 mass% or more of Ca may be added as necessary. However, since excessive addition of Ca leads to a decrease in corrosion resistance, the upper limit of the amount of Ca added is preferably 0.0030 mass%.
[0033] (Zirconium: Zr) Zr is an element that improves high-temperature strength, corrosion resistance, and high-temperature oxidation resistance. In the ferritic stainless steel according to one embodiment of the present invention, 0.01 mass% or more of Zr may be added as necessary. However, since excessive addition of Zr leads to a decrease in workability and manufacturability, the upper limit of the amount of Zr added is preferably 1.0 mass%, and more preferably 0.50 mass%.
[0034] (Hafnium: Hf) Hf is an element that improves corrosion resistance, high-temperature strength, and oxidation resistance. In the ferritic stainless steel according to one embodiment of the present invention, 0.001 mass% or more of Hf may be added as necessary. However, since excessive addition may cause deterioration in workability and manufacturability, the upper limit of the amount of addition is preferably 0.5 mass%.
[0035] (Tin: Sn) Sn is an element that improves corrosion resistance and high-temperature strength. In the ferritic stainless steel according to one embodiment of the present invention, 0.002 mass% or more of Sn may be added as necessary. However, since excessive addition may cause a decrease in toughness and manufacturability, the upper limit of the amount of Sn added is preferably 1.0 mass%.
[0036] (Magnesium: Mg) Mg is a deoxidizing element, and also an element that refines the structure of the slab and improves formability. In the ferritic stainless steel according to one embodiment of the present invention, 0.0003 mass% or more of Mg may be added as necessary. However, since excessive addition of Mg leads to deterioration of corrosion resistance, weldability, and surface quality, the upper limit of the amount of Mg added is preferably 0.0030 mass%.
[0037] (Cobalt: Co) Co is an element that improves high-temperature strength. In the ferritic stainless steel according to one embodiment of the present invention, 0.01 mass% or more of Co may be added as necessary. However, excessive addition of Co reduces toughness and leads to reduced manufacturability, so the upper limit of the amount of Co added is preferably 1.0 mass%, more preferably 0.50 mass%.
[0038] (Antimony: Sb) Sb is an element that improves high-temperature strength. In the ferritic stainless steel according to one embodiment of the present invention, 0.005 mass% or more of Sb may be added as necessary. However, since excessive addition reduces weldability and toughness, the upper limit of the amount of Sb added is preferably 0.50 mass%.
[0039] (Tantalum: Ta) Ta is an element that improves high-temperature strength. In the ferritic stainless steel according to one embodiment of the present invention, 0.001 mass% or more of Ta may be added as necessary. However, since excessive addition reduces weldability and toughness, the upper limit of the amount of Ta added is preferably 1.0 mass%.
[0040] (Gallium: Ga) Ga is an element that improves corrosion resistance and hydrogen embrittlement resistance. In the ferritic stainless steel according to one embodiment of the present invention, 0.0002 mass% or more of Ga may be added as necessary. However, since excessive addition reduces weldability and toughness, the upper limit of the amount of Ga added is preferably 0.30 mass%.
[0041] (Rare earth elements: REM) REM refers to a collective term for scandium (Sc), yttrium (Y), and 15 elements (lanthanoids) from lanthanum (La) to lutetium (Lu). REM may be added as a single element or as a mixture of multiple elements. REM is an element that improves the cleanliness of stainless steel and also improves high-temperature oxidation resistance. In the ferritic stainless steel according to one embodiment of the present invention, 0.001 mass% or more of REM may be added as necessary. However, excessive addition increases the alloy cost and reduces manufacturability, so the upper limit of the addition amount is preferably 0.20 mass%.
[0042] <Method of manufacturing ferritic stainless steel> The ferritic stainless steel according to one embodiment of the present invention is obtained, for example, as a ferritic stainless steel strip. Fig. 1 is a flow chart showing an example of a method for producing the ferritic stainless steel according to this embodiment. As shown in Fig. 1, the method for producing the ferritic stainless steel strip according to this embodiment includes a pretreatment step S1, a hot rolling step S2, an annealing step S3, a pickling step S4, a cold rolling step S5, a final annealing step S6, a nitric acid electrolysis step S7, and a nitric hydrofluoric acid immersion step S8.
[0043] In the pretreatment step S1, first, a melting furnace in a vacuum or argon atmosphere is used to melt steel having a composition adjusted to fall within the range of the present invention, and the steel is cast to produce a slab (steel ingot). Then, a slab piece for hot rolling is cut out from the slab. The slab piece is then heated to a temperature range of 1100°C to 1300°C in an air atmosphere. The time for which the slab piece is heated and held is not limited. When the pretreatment step is carried out industrially, the casting may be continuous casting.
[0044] The hot rolling step S2 is a step of producing a hot rolled steel strip having a predetermined thickness by hot rolling the slab obtained in the pretreatment step S1.
[0045] The annealing step S3 is a step for softening the hot-rolled steel strip obtained in the hot rolling step S2 by heating the steel strip. The annealing step S3 is a step that is performed as necessary, and does not necessarily have to be performed.
[0046] The pickling step S4 is a step in which scale adhering to the surface of the steel strip is washed off using a pickling solution such as hydrochloric acid or a mixture of nitric acid and hydrofluoric acid.
[0047] The cold rolling step S5 is a step in which the steel strip that has been descaled in the pickling step S4 is further rolled to a thinner thickness.
[0048] The final annealing step S6 is a step in which the steel strip rolled in the cold rolling step S5 is heated to remove distortion and soften the steel strip. The annealing in the final annealing step S6 is performed at a temperature of 950 to 1050°C depending on the alloy components.
[0049] The nitric acid electrolysis step S7 and the nitric hydrofluoric acid immersion step S8 are steps for lowering the carbon concentration near the surface of the ferritic stainless steel being produced.
[0050] The nitric acid electrolysis step S7 is a step in which the steel strip obtained in the final annealing step S6 is electrolyzed in an aqueous nitric acid solution. The nitric acid concentration in the nitric acid electrolysis step S7 is 100 g / L or more, preferably 130 g / L or more, and more preferably 150 g / L or more. The solution temperature in the nitric acid electrolysis step S7 is 40° C. or more, and more preferably 50° C. or more. The current density in the nitric acid electrolysis step S7 is 100 mA / cm 2 More than 130mA / cm 2 It is preferable that the current is 150 mA / cm or more. 2It is more preferable that the electrolysis time in the nitric acid electrolysis step S7 is 60 seconds or more. The upper limits of the nitric acid concentration, solution temperature, current density, and electrolysis time in the nitric acid electrolysis step S7 are not particularly limited, but it is preferable that the nitric acid concentration is 250 g / L or less, the solution temperature is 80° C. or less, the current density is 250 mA / cm2 or less, and the electrolysis time is 180 seconds or less.
[0051] The nitric hydrofluoric acid immersion step S8 is a step in which the steel strip after the nitric acid electrolysis step S7 is immersed in nitric hydrofluoric acid, which is a mixed solution of nitric acid and hydrofluoric acid. The nitric hydrofluoric acid used in the nitric hydrofluoric acid immersion step S8 has a nitric acid concentration of 80 to 90 g / L and a hydrofluoric acid concentration of 10 to 20 g / L. The liquid temperature in the nitric hydrofluoric acid immersion step S8 is 30 to 60° C. The immersion time in the nitric hydrofluoric acid immersion step S8 is 40 to 60 seconds, depending on the chemical composition of the ferritic stainless steel.
[0052] The inventors have discovered that by carrying out the nitric acid electrolysis step S7 and the nitric hydrofluoric acid immersion step S8 under the above conditions, it is possible to produce a ferritic stainless steel having a cumulative C concentration measured at 0.0025 μm intervals from the surface to a depth of 0.1 μm of 200 wt% or less.
[0053] In the past, after the cold rolling step S5, a pretreatment was performed in which the steel strip was immersed in an organic solvent or an alkaline solution and washed with a cleaning brush while spraying water in order to remove oil adhering to the surface of the steel strip. In the manufacturing method of ferritic stainless steel of this embodiment, the carbon concentrated on the surface of the ferritic stainless steel can be removed by performing an annealing treatment in a state in which oil is adhering, using the nitric acid electrolysis step S7 and the nitric hydrofluoric acid immersion step S8. Therefore, since there is no need to perform the above-mentioned pretreatment, ferritic stainless steel can be manufactured at low cost. In the conventional method, carbon is concentrated on the surface of the manufactured ferritic stainless steel even if the above-mentioned pretreatment is performed.
[0054] As described above, the ferritic stainless steel of the present invention has a cumulative carbon concentration of 200 wt% or less measured at 0.0025 μm intervals from the surface to a depth of 0.1 μm. This configuration improves red scale resistance. Furthermore, the ferritic stainless steel of the present invention can be manufactured at low cost because it does not require the above-mentioned pretreatment.
[0055] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. EXAMPLES
[0056] An embodiment of the present invention will be described below. Steel materials No. 1 to 56 as an embodiment of the ferritic stainless steel of the present invention or as comparative examples were produced as follows. First, the components shown in Table 1 below were used as raw materials, and the above-mentioned production method was carried out up to the final annealing step S6 under the following conditions. Atmosphere of the melting furnace in the pretreatment process S1: Vacuum Mass of slab piece produced in pre-treatment process S1: 30 kg Heating temperature of slab in pretreatment process S1: 1230℃ Heating time of the slab in pretreatment step S1: 2 hours -Thickness after hot rolling process S2: 4mm Annealing process S3: Not performed Pickling solution used in pickling process S4: Nitric hydrofluoric acid solution (aqueous solution of 3% hydrofluoric acid and 10% nitric acid) - Temperature of pickling solution in the first pickling process S4: 60℃ -Thickness after cold rolling process S5: 1.5mm Annealing temperature in the final annealing process S6: 950 to 1050°C (depending on the alloy composition) In this example, the compositions shown in Table 1 are shown in mass%. The balance other than each component shown in Table 1 is Fe or a small amount of impurities that are inevitably mixed in. The underlines in Table 1 indicate that the range of each component contained in each stainless steel according to the comparative example of the present invention is outside the range of the present invention.
[0057] Next, in order to remove carbon near the surface of the steel strip, the nitric acid electrolysis step S7 and the nitric hydrofluoric acid immersion step S8 were carried out under the following conditions, thereby producing steel materials No. 1 to 56. Nitric acid concentration in nitric acid electrolysis process S7: 150g / L Nitric acid liquid temperature in nitric acid electrolysis process S7: 40 to 60°C Current density in nitric acid electrolysis step S7: 150mA / cm 2 Nitric acid used in the nitric acid soaking process S8: nitric acid 80-90g / L, hydrofluoric acid 10-20g / L Nitric acid temperature in nitric acid immersion process S8: 30 to 60°C The electrolysis time in the nitric acid electrolysis step S7 was 60 seconds as shown in the following Table 2. The immersion time in nitric hydrofluoric acid in the nitric hydrofluoric acid immersion step S8 was 30 to 60 seconds as shown in Table 2. [Table 1]
[0058] [Table 2] For steel materials Nos. 1 to 48, the carbon concentration and Cr concentration near the surface were measured and an oxidation test was performed by the methods described in detail below.
[0059] <Carbon concentration measurement> The carbon concentration near the surface was measured using a glow discharge spectroscopy (GDS) (HORIBA GD-Profiler2). Specifically, the carbon concentration was measured at 0.0025 μm intervals from the surface to a depth of 0.1 μm. The measurement conditions for the GDS measurements were gas replacement time: 200 seconds, pre-sputtering time: 30 seconds, background: 5 seconds, depth: 1.01 μm, pressure: 600 Pa, power: 35 W, effective value: 8.75 W. Module: 8 V, phase: 4 V, frequency: 100 Hz, duty cycle: 0.25. The data of the integrated measured carbon concentration is shown in Table 2.
[0060] <Chromium concentration> An energy dispersive X-ray spectroscopy (EDS) (manufactured by Horiba, Ltd.) was used to analyze the area from the surface to a depth of 1 μm, and the average Cr concentration from the surface to a depth of 1 μm was calculated. The calculated Cr concentration is shown in Table 2.
[0061] <Oxidation test> In order to evaluate the red scale resistance of the steel materials, an oxidation test was carried out using the following method. First, test pieces measuring 20 mm x 25 mm were cut out from each steel material, and only the end faces were dry polished using #400 abrasive paper. Next, each test piece was held in an air atmosphere containing 10% water vapor at 500°C for 100 hours, and the weight increase due to oxidation was measured. The oxidation test was carried out three times for each steel material, and the average weight increase was calculated. The calculated weight increases are shown in Table 2. In this oxidation test, a test piece with a weight increase of 0.1 mg / cm 2 Less than 0.1mg / cm 2 The above was evaluated as × (bad).
[0062] As shown in Table 2, steel materials Nos. 3, 4, 7, 8, 10-12, 15, 16, 18-20, 23, 24, 27, 28, 31, 32, 35, 36, 39, and 40 were produced using steel materials A1-A10 having the composition of the present invention, and had an integrated C concentration of 200 wt% or less measured at 0.0025 μm intervals from the surface to a depth of 0.1 μm. The average Cr concentration from the surface to a depth of 1 μm was 13.0 wt% or more, and the oxidation weight was small. In other words, these steel materials had high red scale resistance.
[0063] On the other hand, in the steel materials using steel types A1 to A10 having the composition of the present invention, in which the integrated value of the C concentration measured at 0.0025 μm intervals from the surface to a depth of 0.1 μm was greater than 200 wt%, the average Cr concentration from the surface to a depth of 1 μm was less than 13.0 wt%, and the oxidation weight gain was large.
[0064] Steel Nos. 41 to 44, which were made using steel type B1, had low red scale resistance due to the small amount of Cr and Si. Steel Nos. 45 to 48, which were made using steel type B2, Surface area calculation C concentration was high Therefore, the red scale resistance was low. Steel materials No. 49 to 52, which were made using steel type B3, had a high Cr content, so the oxide scale formed during annealing could not be completely removed by final pickling. As a result, a large amount of C remained, creating an unstable surface condition in which sound Cr-based oxides could not be formed, and the red scale resistance was low. Steel materials No. 53 to 56, which were made using steel type B4, Surface area calculation C concentration was high In the steel materials No. 47, 48, 50 to 52, and 56, the average Cr concentration from the surface to a depth of 1 μm was 13.0 wt% or more, but because carbon had not been sufficiently removed, the red scale resistance was low.
Claims
1. the composition contains, by mass%, C: 0.040% or less (excluding 0%), Si: 0.01 to 1.0% or less, Mn: 0.03 to 2.0%, P: 0.05% or less (excluding 0%), S: 0.005% or less (excluding 0%), Ni: 1.5% or less (excluding 0%), Cr: 13 to 26.0%, Cu: 2.0% or less (excluding 0%), N: 0.040% or less (excluding 0%), Mo: 2.5% or less (excluding 0%), Nb: 1.0% or less (excluding 0%), Ti: 0.5% or less (excluding 0%), and Al: 0.002 to 0.1% or less, with the balance being Fe and unavoidable impurities; A ferritic stainless steel having a carbon concentration of 200 wt % or less, calculated by accumulating carbon concentrations measured at 0.0025 μm intervals from the surface to a depth of 0.1 μm.
2. 2. The ferritic stainless steel according to claim 1, further containing, by mass%, one or more of 0.01% or less B (excluding 0%), 0.0002% to 0.0030% or less Ca, 0.001% or more and 0.5% or less Hf, 0.01% or more and 1.0% or less Zr, 0.005% or more and 0.50% or less Sb, 0.01% or more and 1.0% or less Co, 0.01% or more and 2.0% or less W, 0.001% or more and 1.0% or less Ta, 0.002% or more and 1.0% or less Sn, 0.0002% or more and 0.30% or less Ga, 0.001% or more and 0.20% or less rare earth elements, and 0.0003% or more and 0.0030% or less Mg.
3. A steel sheet having, by mass%, C: 0.040% or less (excluding 0%), Si: 0.01 to 1.0% or less, Mn: 0.03 to 2.0%, P: 0.05% or less (excluding 0%), S: 0.005% or less (excluding 0%), Ni: 1.5% or less (excluding 0%), Cr: 13 to 26.0%, Cu: 2.0% or less (excluding 0%), N: 0.040% or less (excluding 0%), Mo: 2.5% or less (excluding 0%), Nb: 1.0% or less (excluding 0%), Ti: 0.5% or less (excluding 0%), and Al: 0.002 to 0.1% or less, and optionally containing B: 0.01% or less (excluding 0%), and 0.0002% to A steel strip that is annealed after cold rolling and contains one or more of 0.0030% or less Ca, 0.001% or more and 0.5% or less Hf, 0.01% or more and 1.0% or less Zr, 0.005% or more and 0.50% or less Sb, 0.01% or more and 1.0% or less Co, 0.01% or more and 2.0% or less W, 0.001% or more and 1.0% or less Ta, 0.002% or more and 1.0% or less Sn, 0.0002% or more and 0.30% or less Ga, 0.001% or more and 0.20% or less rare earth elements, and 0.0003% or more and 0.0030% or less Mg, with the balance being Fe and unavoidable impurities, is immersed in a nitric acid aqueous solution having a concentration of 100 g / L or more and a liquid temperature of 40° C. or more, at a current density of 100 mA / cm 2 The above is a nitric acid electrolysis step in which electrolysis is performed for 60 seconds or more; a nitric / hydrofluoric acid immersion step of immersing the steel strip after the nitric acid electrolysis step in a mixed solution of nitric acid and hydrofluoric acid, the mixed solution having a nitric acid concentration of 80 to 90 g / L, a hydrofluoric acid concentration of 10 to 20 g / L, and a solution temperature of 30 to 60° C., for 40 to 60 seconds; The integrated value of the C concentration measured at 0.0025 μm intervals from the surface to a depth of 0.1 μm is 200 wt% or less, and the following mass percentages are used: C: 0.040% or less (excluding 0%), Si: 0.01 to 1.0% or less, Mn: 0.03 to 2.0%, P: 0.05% or less (excluding 0%), S: 0.005% or less (excluding 0%), Ni: 1.5% or less (excluding 0%), Cr: 13 to 26.0%, Cu: 2.0% or less (excluding 0%), N: 0.040% or less (excluding 0%), Mo: 2.5% or less (excluding 0%), Nb: 1.0% or less (excluding 0%), Ti: 0.5% or less (excluding 0%), and Al: 0.002 to 0.1% or less. and optionally containing one or more of 0.01% or less B (excluding 0%), 0.0002% to 0.0030% or less Ca, 0.001% or more and 0.5% or less Hf, 0.01% or more and 1.0% or less Zr, 0.005% or more and 0.50% or less Sb, 0.01% or more and 1.0% or less Co, 0.01% or more and 2.0% or less W, 0.001% or more and 1.0% or less Ta, 0.002% or more and 1.0% or less Sn, 0.0002% or more and 0.30% or less Ga, 0.001% or more and 0.20% or less rare earth elements, and 0.0003% or more and 0.0030% or less Mg, with the balance being Fe and unavoidable impurities.
Citation Information
Patent Citations
Pickling method for ferritic stainless steel hot rolled stock
JP1993230681A
Ferritic stainless steel sheet excellent in weatherability and its manufacture
JP1993271880A
Highly corrosion-resistant ferritic stainless steel and its production
JP1994346195A
Ferritic stainless steel excellent in corrosion resistance and its production
JP1994346197A
Stainless steel excellent in elution resistance of metallic ion and its production
JP2000345301A